Qualitative Analyses of the Required Leadership Skills of Academics Working in the Education Sector in India - Singh Thakur, Anand (Digital Repository of Theses, 2026)
This dissertation examines the leadership skills, decision making styles and learning abilities needed by academic leaders in Indian Higher education. Considering a qualitative approach with semi-structured interviews, questionnaires, and document analysis, the study has determined five core competencies, including strategic vision and planning (85%), decision-making and problem-solving (80%), innovation and continuous learning (75%), empathy and mentorship (72%), and adaptability to change (70%). The competencies affirm the transformation of the hierarchical, authority-based models of governance into the participatory, evidence-based, and results-based leadership. The study points out that peer consultation (26%) and stakeholder engagement as the most common practice (24%) seem to be the most acceptable decision making and the systematic evaluation (22%), evidence-based methods (14%), are the response to the increasing dependence on transparent governance. Organisational learning was also found to be important and institutions laying stress on comparative training examination, use of skills, development indicators and feedback systems to improve leadership execution. The results add to the literature by putting the existing global leadership theories into context with the Indian higher education system and to practice by generating practical action recommendations. Managerial implications are that it requires formalized decision protocols, mentoring architectures and capability building pathways. The relevance of policies to those of NEP 1986 and NEP 2020 (National Education Policy 2020) that highlight autonomy, inclusivity, and adoption of digital are reflected (Government of India, 2020; Government of India, 1986). Generally, the paper offers a competency-based model of enhancing academic leadership in India, institutional sustainability, policy responsiveness, and competitiveness in a global academic environment.